Effects of four anaesthetic protocols on the neurological and cardiorespiratory variables of puppies born by caesarean section - Luna, S. P.; Cassu, R. N.; Castro, G. B.; Teixeira Neto, Francisco José [UNESP]; Silva, JR; Lopes, Maria Denise [UNESP] (British Veterinary Assoc, 2004)
Twenty-four bitches which had been in labour for less than 12 hours were randomly divided into four groups of six. They all received 0(.)5 mg/kg of chlorpromazine intravenously as premedication, followed 15 minutes later by either 8 mg/kg of thiopentone intravenously (group 1), 2 mg/kg of ketamine and 0-5 mg/kg of midazolam intravenously (group 2), 5 mg/kg of propofol intravenously (group 3), or 2(.)5 mg/kg of 2 per cent lidocaine with adrenaline and 0(.)625 mg/kg of 0(.)5 per cent bupivacaine with adrenaline epidurally (group 4). Except for group 4, the bitches were intubated and anaesthesia was maintained with enflurane. The puppies' heart and respiratory rates and their pain, sucking, anogenital, magnum and flexion reflexes were measured as they were removed from the uterus. The puppies' respiratory rate was higher after epidural anaesthesia. in general the puppies' neurological reflexes were most depressed after midazolam/ketamine, followed by thiopentone, propofol and epidural anaesthesia.